Digital Marketing Strategy in the Online Fashion Industry - Wahyu Sri Handono; Anthoneta Kopong; Muhammad Nur Madani (Lembaga Komunitas Informasi Teknologi Aceh (KITA), Indonesia, 2024)
The online fashion industry is rapidly growing due to advancements in digital technology and changes in consumer behavior. This article explores effective digital marketing strategies to enhance the visibility and competitiveness of online fashion businesses, with a focus on SMEs. These strategies include the use of digital advertising, social media, and marketplaces. Social media, particularly Instagram, is highly effective in building brand awareness and increasing engagement through features like Stories, Reels, and Shopping. The COVID-19 pandemic accelerated the adoption of digital marketing as a primary solution to maintain business continuity. Training in digital marketing strategies is crucial for SMEs to understand and apply effective techniques such as SEO, SEM, and content marketing. SEO improves website rankings in search results, SEM uses paid ads for quick results, and content marketing focuses on creating relevant content. Digital analysis tools like Google Analytics help companies understand content performance and make necessary adjustments. With the right strategy, online fashion companies can achieve success in the digital era.